HUBUNGAN MINAT BACA DENGAN KETERAMPILAN MENULIS RINGKASAN SISWA KELAS V SDN 16 PADANG BESI - Ayu Sartika, Putri; Muhammadi; Azmi Alwi, Nur; Yenti, Yesni; Habibi, M (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted to determine the relationship between reading interest and summary writing skills of fifth-grade students at SDN 16 Padang Besi in the 2025/2026 academic year. The study used a quantitative approach with a correlational design. The research sample consisted of 27 students. Data were collected using a reading interest questionnaire and a summary writing test. Data analysis used descriptive statistics and the Spearman correlation test. The results showed a positive and significant relationship between reading interest and summary writing skills with a correlation coefficient value of 0.952 and a significance of 0.000 <0.05. This value indicates a relationship in the very strong category with a contribution of 90.6%. The higher the students' reading interest, the better their summary writing skills.